Variaciones estacionales de la estructura comunitaria del fitoplancton en zonas de descarga de agua subterránea en la costa norte de la Península de Yucatán - Álvarez-Góngora, Cynthia Catalina (2012)
Abstract: Seasonal variations of community structures phytoplankton in groundwater discharge areas along the Northern Yucatán Peninsula coast. The highly touristic Yucatán Peninsula is principally constituted with coastal marine environments. Like other coastal areas, this has been affected by the increase of waste water discharge, hydrological modifications and land use changes in the area. The phytoplankton community structure is one of the main components of coastal ecosystems and the most affected in hydrological processes. In order to follow the seasonal variations, the phytoplankton was characterized to follow the hydrological variability in two sites (Dzilam and Progreso) of the Northern Yucatán Peninsula. For this, cruises were carried out monthly during one year, from April 2004 to March 2005, with two samplings per season (dry, rainy and “nortes”). Hydrological variability was associated with seasonality and directly linked to groundwater discharges in the Dzilam area, and waste water discharges in the Progreso area. The highest nutrient concentrations occurred mainly during the rainy season. The phytoplankton community changes observed throughout the year suggested that the hydrological and chemical variability associated with seasonality and anthropogenic impacts have a strong influence. The substitution of diatoms by dinoflagellates as the dominant group in Progreso was the result of seasonal variability itself, but also could have been caused by eutrophic processes; while in Dzilam, the major presence of diatoms could have been favored by groundwater discharges. The results of this study can be used to understand the linkages between stressors from the anthropogenic activities and coastal water quality and changes.